Assessing the viability of a grid-connected PV power plant in Mubi, Adamawa State, Nigeria - Luqman, Raji; Kehinde Issa, Abdul-Jeleel; Owolabi, Abdulhameed Babatunde; Yakub, Abdulfatai Olatunji; Same, Noel Ngando; Yahaya, Abdullahi; Yasin, Naveed; Kavgic, Miroslava; Suh, Dongjun; Huh, Jeung-Soo (Frontiers in Energy Research, 2023)
This paper is based on a techno-economic analysis and the environmental impact of a proposed 1 MW solar photovoltaic (PV) power plant at the main campus of the Federal Polytechnic Mubi (FPM) in north-eastern Nigeria. A photovoltaic power plant converts solar radiation into electricity that can be used as a source of electrical power to meet the daily energy requirements of homes, equipment, and all tertiary institutions. RETScreen Expert software was used to evaluate the techno-economic and environmental sustainability of installing a grid-connected PV power plant. The research results revealed that with an annual solar radiation of 5.74 kWh/m2/day, the maximum annual energy production was estimated to be 1,550.98 MWh. It was discovered that the maximum energy production in March was 146.89 MWh. The project’s profitability and economic sustainability were determined with a good internal rate of return (IRR) of 11.9% and a positive net present value (NPV) of 681,164. The proposed PV power plant has a simple payback period of 11.4 years. The maximum greenhouse gas (GHG) emission reduction is 670.9 tCO2, equivalent to 61.7 ha of forest-absorbing carbon emissions.